Energy Efficient Scheduling Algorithm To Increase The Life Time Of Battery Power In Wireless Sensor Networks For Structural Health Building Monitoring Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Because of its ability to reduce the costs associated with the installation and maintenance of SHM systems, structural health monitoring using wireless sensor networks has piqued researchers' interest. These systems are used to monitor critical infrastructure like high-rise buildings, bridges, and stadiums, and they have the potential to extend the life of structures and improve public safety. WSNs for SHMs face unique network design challenges due to their high data collection rate. This paper provides a comprehensive overview of SHM using WSNs, including a description of the algorithms used in physical harm detection and localization, network design issues, and future systematic investigation directions. Time synchronization, sensor placement, data processing, and quantifiability are all discussed and compared as network design issues. For improving the lifespan of a wireless sensor network, the proposed framework includes four stages: node investigation and deployment, clustering nodes, shortest path construction, and data transmission. This paper proposes a novel framework that consists of four stages: optimal node deployment, clustering of nodes, shortest route construction, and data transmission. It's built into the NS2 software, and the results are double-checked. Finally, the proposed framework's performance is assessed by comparing its results to those of other approaches and demonstrating its efficiency